(untitled) (Bangladesh Journal of Urology, 2020)
Objective: The present prospective study was conducted to evaluate the renal function after percutaneous nephrostomy (PCN) in obstructive uropathy due to ureteropelvic junction obstruction. Patients of UPJ obstruction irrespective of sex upto 15 years of age and split renal function (SRF) of the affected kidney <10% were enrolled in the study. Methods: The present prospective study was carried out at the Department of Urology, Dhaka Medical College Hospital from January 2007 to December 2008. The patients having ureteropelvic junction (UPJ) obstruction with poor renal function were the study population. Patients of either sex up to 15 years of age and split renal function < 10% (unilateral and / bilateral) were enrolled in the study. Patients with other anatomical abnormality of urinary system, concomitant pathologies like stone, pyonephrosis or previous surgical intervention of kidney and/or ureter were excluded from the study. Baseline variables were flank mass, flank pain, side of hydronephrosis, split renal function (SRF), glomerular filtration rate (GFR), specific gravity of urine at the time of PCN. Postoperative follow up variables (at 2, 4 and 6 weeks) were split renal function (SRF), glomerular filtration rate (GFR), specific gravity urine draining through nephrostomy tube, volume of urine through nephrostomy tube and complications. Data were collected using a structured questionnaire (research instrument) containing all the variables of interest. Data were processed and analysed using SPSS (Statistical Package for Social Sciences). The test statistics used to analyse the data were descriptive statistics and Repeated measure ANOVA. For all analytical tests, the level of significance was set at 0.05 and p < 0.05 was considered significant. Result: The mean age of the patients was 8.6 ± 3.9 years and the lowest and highest ages were 3 months and 15 years respectively. The poorly functioning kidneys demonstrated a steady increase in SRF from 3.6% at baseline to 23% after 6 weeks PCN (p < 0.001). SRF of all children except 4 improved significantly during the period. The mean GFR of poorly functioning kidneys was 3.5ml/min/1.73 sq-meter at baseline which increased to 28.4 ml/min/1.73 sq-meter at the end of week 6. The GFR of 34 children improved (> 10 ml/min/1.73 sq-meter at the 6 week of treatment. Four cases (10.5%) did not improve. The specific gravity of urine significantly increased from 1.009 at baseline to 1.019 after 6 weeks. The volume of urine at 2nd week was 338 ml/24hour which sharply increased to 363 ml/24 hours at week 4 and nearly 386 ml/24hours after 6 weeks of PCN (p < 0.001). Conclusion: Present study recommends that as the likelihood of recovery of a severely damaged kidney (SRF < 10%) with UPJO following PCN is fairly satisfactory; none of the children with poorly functioning kidney should undergo nephrectomy without subjecting them to a PCN trial. Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.36-41